Integrasi Fikih dan Tasawuf Perspektif Tarekat Tijaniyyah - Muhammad Fahri Yahya (Jurnal Penelitian Ilmu Ushuluddin, 2022)
Ascetic practice that focuses on inner charity (Sufism) in worshiping Allah. without carrying out worship related to the external aspect (Fiqh) is still carried out among Muslims themselves. How is the view of the Tijaniyyah Order in responding to the phenomena that occur? This study aims to analyze the concept of harmony in the practice of fiqh and tasawuf from the perspective of the Tijaniyyah Order. This study applies qualitative methods and uses literature research objects which are categorized as library research. The results and discussion of this study show the concept of harmony in the practice of Sufism and fiqh in the Tijaniyyah Order and discuss the biography of Sheikh Ahmad Attijani as the founder of the at-Tijani congregation. The conclusion of this study explains that the Tijaniyyah Order applies religious practices based on fiqh and Sufism as physical and spiritual deeds. This research recommends for further research with a holistic perspective.